Evaluation of some physical properties of an oxisol after conversion of native savanna into legume-based or pure grass pastures - Gijsman, A.J.; Thomas, Richard J. (1996)
This study evaluated the effects of improved tropical grass and grass–legume pastures on the physical condition of an oxisol, previously covered by native savanna. Two long-term pasture experiments with different grass and legume species and with different stocking rates were used. Measurements were made of bulk density, penetrometer resistance, water retention characteristics, total porosity, pore-size distribution and water infiltration rate. The bulk density of the 0–5 cm and 6–11 cm layers was not affected by any of the treatments. Penetrometer resistance was affected by presence of a legume and stocking rate, but differences were small and of little practical importance. There was no difference in water retention curves between the pure grass and grass-legume treatments. The decline in water content with increasing pF occurred more gradually in the low-stocking-rate treatments than in the high-stocking-rate treatments or the native savanna. Consequently, the amount of plant-available water was smaller in the former treatments. The water infiltration rate was higher under grass–legume than under pure grass pastures and decreased with increasing stocking rate under both types of pastures. Differences in soil physical properties are explained by differences in root systems between the two types of pastures, and by differences in biomass, composition and distribution of soil fauna, especially earthworms. The implications of this work for decreasing soil erosion are stressed.